Strontium ranelate, a promising disease modifying osteoarthritis drug. (4th March 2017) - Han, Weiyu; Fan, Shicai; Bai, Xiaochun; Ding, Changhai
ABSTRACT: Introduction : The articular cartilage and subchondral bone may have potential crosstalk in the development and progression of osteoarthritis (OA). Strontium ranelate (SrR) has the ability to dissociate the bone remodeling process and to change the balance between bone resorption and bone formation. Its effect on subchondral bone makes it a potential disease- modifying osteoarthritis drug (DMOAD) in the treatment of OA. The aim of the current review is to summarize up-to-date pharmacological and clinical data of SrR for OA treatment. Areas covered : A literature search was performed on PubMed and European Medicines Agency (EMA) website for all publications and documents related to SrR and OA. References of related studies were searched by hand. Treatment with SrR, especially at the dosage of 2 g/day, was associated with reduced radiographic knee OA progression, and with meaningful clinical improvement. It was also significantly associated with decreased MRI-assessed cartilage volume loss (CVL) and bone marrow lesions (BMLs). Expert opinion : SrR could be a promising DMOAD particularly for OA patients with bone phenotypes. The clinical efficacy and side effects of SrR for OA treatment need to be further investigated in future clinical trials before clinical application.